Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Transport of metal ions through cellulose fiber supported solid membrane into tributyl phosphate containing mixed solvents - Gaikwad, Abaji G. (Chemical and Biochemical Engineering Quarterly, 2011)
A novel cation exchange fiber supported solid membrane was developed for transport of cobalt, manganese and nickel metal ions. Fiber supported solid membrane was prepared by chemically modifying the cellulose fibers with citric acid. In the fiber supported solid membrane, the diffusion by capillary action by keeping the liquid phase in the porous solid fiber and ion exchange mechanism were used for the effective transport of metal ions. The experimental variables examined were concentration of metal ions (10(-2) to 10(-4) mol L-1) in the source solution, mixed solvent composition (phi = 20 % TBP, acetone or tetrahydrofuran or 1,4-dioxane or methanol or ethanol or 2-propanol 10 to 60 % and HCl (1 to 2 mol L-1) in the receiving phase and stirring speed (40-120 rpm) of the bulk source and receiving phase. The enrichment of concentration of cobalt, manganese and nickel metal ions was observed from the dilute solutions.
Keywords: binary of mixtures of metal ions; cobalt; extraction; fiber supported solid membrane; ion exchange; manganese and nickel metal ions; stripping

Transport of metal ions through fiber supported solid membranes in mixed solvents - Gaikwad, Abaji G. (Fibers and Polymers, 2011)
The transport of metal ions has been explored of bismuth, cadmium and lead from source solution to receiving phase through the fiber supported solid membrane system. The fibers supported solid membranes were prepared by chemically modification of cellulose fibers with the introducing the ion exchanging groups. The experimental variables explored were concentration of metal ions in the source solution, mixed solvent composition in the receiving phase and stirring speed of the bulk source solution and receiving phase. The efficiency has been evaluated for the transport of metal ions from the source to receiving phase through the fiber supported solid membrane. The pre-concentration was investigated of metal ions from the dilute solutions. The fiber supported solid membrane with two-channel systems had been investigated for the transport of metal ions from the source to receiving phase. The capillary action phenomenon helps to effectively transport the metal ions through the fiber supported solid membrane.
Keywords: binary of mixtures of metal ions; Bismuth; Cadmium and lead metal ions; extraction; fiber supported solid membrane; ion exchange; stripping